Perilaku Sosial Tokoh Utama Novel Berteman Dengan Kematian Catatan Gadis Lupus Karya Sinta Ridwan - Azzellya, Putri (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study aims to determine the social behavior contained in the novel Death Note Girl Friend With Lupus works Sinta Ridwan, with an overview of Psychology literature so that the novel can be used as teaching material in high school literature appreciation. The method used in this research is descriptive with content analysis techniques. The object of this study is novel Death Note Girl Friend With Lupus works Sinta Ridwan. The focus in this study social behavior and examines the psychology literature in the novel. Trends in social behavior include Role, Sosiometrik trend, trend Expression. In psychology literature covering Id, Ego, Super Ego. The research instrument that is the researchers themselves who assisted with analysis tables based on the focus of research. Issues addressed in this study is the first, How novel structure depicted in the novel as Friend With Death Note Lupus Girl ?. Second, How novel social behavior Friend With Death Note Lupus Girl ?. Third, How social behavior in the study of psychology literature novel Death Note Girl Friend With Lupus? The results of this study are expected to increase students' interest in reading, especially reading literary novels. In addition to further improve the teachers teaching literature appreciation by using a more varied and effective, so as to increase students' interest towards learning literature appreciation.